PSYCHOLOGICAL FACTORS OF SLEEP QUALITY - Denisiievska Anna (International Journal of Innovative Technologies in Social Science, 2021)
The article describes some psychological factors of sleep quality. Theoretical analysis of psychological factors that affect the quality of sleep is presented. Sleep quality is an important part of a person's overall health. Sleep problems can be associated with decreased physical and mental health, limitations in daily activities, cognitive impairment. Given these consequences, there is a need for a better understanding of the factors associated with the improvement and deterioration of sleep quality. The relevance of this problem in the context of modern research. The results of an empirical study that reveals the relationship between sleep quality and some psychological factors are highlighted. It was found that the average score of sleep quality indicates unsatisfactory sleep quality. It was found that there are significant differences between the groups of subjects with satisfactory and unsatisfactory indicators of the overall score of sleep quality on the scales of neuroticism and depression. In people who are dissatisfied with the quality of sleep, the level of neuroticism is close to high and there is moderate depression. The relationships between sleep quality indicators and psychological factors have been identified, and their features have been analyzed. In general, these relationships demonstrate: emotional inadequacy does not contribute to a better subjective quality of sleep; depressive or anxious symptoms, emotional instability do not contribute to rapid falling asleep, but contribute to sleep disorders and daytime dysfunction; anxious characteristics affect the reduction of sleep time.